Analisis Strategi Tax Planning PT Merck Tbk: Keseimbangan antara Kepatuhan dan Efisiensi Fiskal - Jeanni Otyne D.S.; Ida Farida Adi Prawira; Memen Kustiawan (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
This study aims to assess the effectiveness of tax planning strategies in enhancing fiscal efficiency at PT Merck Tbk, a pharmaceutical company with a complex cost structure that often generates positive fiscal corrections due to improper expense classification and insufficient documentation. Addressing a gap in prior research that generally relies on macro-level indicators, this study emphasizes account-level analysis. A qualitative descriptive approach was employed using secondary data from the company’s 2023 and 2024 income statements and fiscal reconciliation documents. A before–after analysis was conducted to evaluate changes in deductible expenses, fiscal corrections, and income tax burdens. The results indicate that restructuring in-kind employee benefits to comply with regulations, preparing nominative lists for promotional activities, and reclassifying miscellaneous operating expenses into tax-allowable categories substantially reduced permanent fiscal corrections; two categories were completely eliminated and one reduced by approximately 50%. These adjustments lowered pre-tax income and generated tax savings of Rp6,616,233 in 2023 and Rp10,076,300 in 2024. The findings demonstrate that tax planning not only reduces tax liabilities but also strengthens compliance through improved documentation and expense classification, offering practical guidance for firms to optimize their tax positions legally.